Mathematical modeling of drying kinetics of grapefruit peels (Citrus paradisi Macf.) (Research, Society and Development, 2020)
The objective of the present study was to characterize physically the grapefruit peel (Citrus paradisi Macf.) and to model the drying of the dehydrated samples at 60, 70, 80 and 90 ºC, evaluating the model adjustments and the drying rates, in their respective temperatures. In natura barks were characterized by water content, total and soluble solids, water activity, ash, pH, total titratable acidity, Ratio and ascorbic acid. The drying kinetics were performed in an air circulation oven, adjusting eleven mathematical models, considering as fit quality criterion, the determination coefficients (R2) and the mean square deviations (DQM). Grapefruit peels showed high water content and water activity, low acidity and ashes. Ten of the models presented satisfactory adjustments to the drying kinetics, highlighting Page, Logarithmic, Diffusion Approximation and Midilli, with R2> 0.99 and DQM